'Opera and …': The Pleasures and Perils of Amalgamation. (July 2020) - Parker, Roger
Abstract : We might start with the Index, often a good indicator of a book's flavour, its local habitation. First up is 'Abbate, acoustics, acting, Adler, Adorno', a reassuring miscellany; later on, the German-speaking collective of 'Schopenhauer, Schreker, Schubart, Schumann-Heink' awakens memories of time past. 'Ventilation systems, Verdi, vitalism', however, turns on the landing lights for a distinctly new approach, while 'hygiene [both mental and moral], hyperacusis, hyperaesthesia acoustica, hypnosis, hysteria' ushers in another region entirely: medicine, pathologies. Starting at the end, we are thus prepared: a sense of anticipation is allied to hopes of intriguing surprises in the offing. And such expectations are on the whole justified. In spite of its title – that fence-sitting conjunction – this collection is a worthy and serious attempt to write new chapters in musicology's revolving challenge to the internalist preoccupations of its past.